The agile marketer - Smart, Roland
"The marketer's guide to modernizing platforms and practices Marketing in the digital era is a whole new game: it's fundamentally about competing on the customer experience. Marketers must integrate a complex set of technologies to capture the customer's digital body language--and thereby deliver the right experiences, at the right times, via the right channels. This approach represents a formidable technological and practical challenge that few marketers have experience with. The methods that enable marketers to meet this challenge are emerging from an unexpected place: the world of software development. The Agile methodologies that once revolutionized software development are now revolutionizing marketing. Agile provides the foundation for alignment between the marketing and product management sides. It can unleash a whole array of new marketing opportunities for growth hacking as well as for "baking" marketing directly into your products or services. Beyond that, as a discipline it can serve as a bridge to strategic alignment, positioning the chief marketing officer alongside the chief product officer as the two primary drivers of the business. Written by a premier practitioner of modern marketing, this book will provide you with: Insights on the evolution of product development and management in the organization--and why marketing must partner with them in the new era An understanding of Agile methods and their application to marketing A plan for integrating Agile with your traditional methods Tactics to drive alignment with product management A pathway to becoming the steward of customer experience Rich with examples, case studies, illustrations, and exercises drawn from the author's wide-ranging experience (from startups to a top global technology company), The Agile Marketer will help you transform marketing in your organization, in spirit and practice--and help realize its critical roles in product management and the customer experience"--
"This book is for marketing leaders who are attempting to modernize their marketing practices,the platforms that support them- so that they can partner with the chief poduct officer to innovate, drive the business, and establish competitive advantage. It's also for marketers who recognize a unique opportunity to position marketing as the "steward" not just of the brand but of customer experience across the board"--
Keywords: Product management; Marketing; Strategic planning; BUSINESS & ECONOMICS / Marketing / General